PENGARUH VARIASI KONSENTRASI CAIRAN PENYARI ETANOL TERHADAP KADAR POLIFENOL PADA DAUN BIDURI (Calotropis gigantea L.) - Asriani Suhaenah (Fakultas Farmasi UMI, 2016)
Effect of ethanol concentration variations on levels of polyphenols in the Biduri leaves extract (Calotropis gigantea L.), with the aim to determine the concentration of ethanol that produce high levels of polyphenols maximum on Biduri leaves extract (Calotropis gigantea L.). The method used in the form of laboratory experimental method, which leaves Biduri (Calotropis gigantea L.) is made in the form of extracts by using a variation of ethanol that is 50% ethanol, 70% and 96%, then the variation of the extract polyphenols quantitative test conducted using standard gallat acid and Folin -ciocalteau reagen with UV-VIS spectrophotometry method. The results of quantitative analysis by UV-VIS spectrophotometry method at the maximum wavelength 730 nm, obtained polyphenol content of 50% ethanol to extract mgGAE 11.14 / gram extract, 70% ethanol extract mg GAE 16.20 / gram extract, and 96% ethanol extract 11 , 72 mgGAE / gram of extract. Maximum levels of polyphenols contained in the ethanol extract with a concentration of 70%. Based on statistical analysis, the results obtained polyphenol content of ethanol Biduri leaves extract (Calotropis gigantea L.) with the third variation of the concentration that is 50%, 70%, and 96% were significantly different.